2021
DOI: 10.1080/21655979.2021.2008694
|View full text |Cite
|
Sign up to set email alerts
|

Proto-oncogene tyrosine-protein kinase SRC (Src) inhibition in microglia relieves neuroinflammation in neuropathic pain mouse models

Abstract: Chronic neuroinflammation is an important factor in the development of neuropathic pain (NP). Excess microglia activation releases a mass of pro-inflammatory cytokines during neuroinflammation process, leading to a constant painful irritation of the sensory nerve. Src belongs to a non-receptor tyrosine kinase associated with sarcoma, whereas the role of Src in neuropathic pain is controversial. We designed to testify the inflammation-regulatory role of Src in the lipopolysaccharide (LPS)-induced BV2 microglia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…SRC is a tyrosine kinase involved in a variety of cellular processes [24] and it has been reported to mediate inflammatory responses. Animal experiments have shown that inhibition of SRC expression can reduce microglia-induced neuroinflammation and has a protective effect on a mouse model of neuropathic pain [25] . At the same time, studies have shown that abnormal immune metabolism of Clusters of differentiation 4 + (CD4 + ) T cells and their subsets can affect the occurrence and development of SLE [26] , and the expression of SRC is also related to cell metabolism regulation [27] .…”
Section: Resultsmentioning
confidence: 99%
“…SRC is a tyrosine kinase involved in a variety of cellular processes [24] and it has been reported to mediate inflammatory responses. Animal experiments have shown that inhibition of SRC expression can reduce microglia-induced neuroinflammation and has a protective effect on a mouse model of neuropathic pain [25] . At the same time, studies have shown that abnormal immune metabolism of Clusters of differentiation 4 + (CD4 + ) T cells and their subsets can affect the occurrence and development of SLE [26] , and the expression of SRC is also related to cell metabolism regulation [27] .…”
Section: Resultsmentioning
confidence: 99%
“…SRC inhibition has been reported to play a protective role in a mouse model with NP by reducing microglia-induced neuroinflammation. 32 BCL2 is an anti-apoptotic protein that plays a key role in apoptosis regulation. 33 Ajugarin-I inhibits vincristine-induced NP by modulating Nrf2/NF-κB and BCL2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular damage leads to cytokine necrosis, which causes apoptosis and further aggravates neuroinflammation. This forms a recurrent cycle ( Figure 7 ) that eventually induces central and peripheral sensitization, leading to NP ( 19 , 20 ). According to the keyword analysis, MS, PD, and AD were the three categories of neurodegenerative diseases with the highest attention in this field.…”
Section: Discussionmentioning
confidence: 99%